Flooding and poverty: Two interrelated social problems impacting rural development in Tsholotsho district of Matabeleland North province in Zimbabwe - Dube, Ernest; Mtapuri, Oliver; Matunhu, Jephias (AOSIS (pty) Ltd, 2021)
Flooding and poverty are the two social problems that have coexisted within the rural communities of Tsholotsho district. As a result, both problems have negatively affected and disrupted the everyday lives of people living in the district. This study highlights how the two problems combine to impact human societies.